Learning From Human Responses to Deconditioning Environments: Improved Understanding of the "Use It or Lose It" Principle - David A. Hart; David A. Hart; David A. Hart; David A. Hart (Frontiers Media S.A., 2021)
Physical activity, mobility or patterned mobility (i.e., exercise) is intrinsic to the functioning of Homo sapiens, and required for maintenance of health. Thus, systems such as the musculoskeletal and cardiovascular systems appear to require constant reinforcement or conditioning to maintain integrity. Loss of conditioning or development of chronic deconditioning can have multiple consequences. The study of different types of deconditioning and their prevention or reversal can offer a number of clues to the regulation of these systems and point to how deconditioning poses risk for disease development and progression. From the study of deconditioning associated with spaceflight, a condition not predicted by evolution, prolonged bedrest, protracted sedentary behavior, as well as menopause and obesity and their consequences, provide a background to better understand human heterogeneity and how physical fitness may impact the risks for chronic conditions subsequent to the deconditioning. The effectiveness of optimized physical activity and exercise protocols likely depend on the nature of the deconditioning, the sex and genetics of the individual, whether one is addressing prevention of deconditioning-associated disease or disease-associated progression, and whether it is focused on acute or chronic deconditioning associated with different forms of deconditioning. While considerable research effort has gone into preventing deconditioning, the study of the process of deconditioning and its endpoints can provide clues to the regulation of the affected systems and their contributions to human heterogeneity that have been framed by the boundary conditions of Earth during evolution and the "use it or lose it" principle of regulation. Such information regarding heterogeneity that is elaborated by the study of deconditioning environments could enhance the effectiveness of individualized interventions to prevent deconditions or rescue those who have become deconditioned.